HBASE Data Security with AES Algorithm (International journal of recent technology and engineering, 2020)
Since last decade almost every organization is focusing more on collecting their data (big data) and making analysis of it also applying the concluded valuable outcomes over their organization. The use of smartphones and smart gadgets fasten the gathering of data and enhances the three basic Vs (Volume/ Velocity/ Variety) of big data. This paper focuses on big data security but without fourth V i.e. Value within data, there is no need of securing big data. Perhaps this may be the reason why Hadoop have no security mechanism within its architecture since initially the focus of big data is on the basis of three basic Vs only. With this paper, here authors’ try to provide security to big data by using AES algorithm over HBase database. Authors just giving an idea of big data security methodology and for that the main focus of data security is only on valuable contents of the database.